PERUBAHAN PARAMETER BIOGEOFISIK DAN LINGKUNGAN TPA SAMPAH LEUWIGAJAH PASCA BENCANA LONGSOR - Wahyu Purwanta (BPPT)
This study is conduct to evaluate the changes of biogeophysical aspects of Leuwigajah Dumping Area (TPA) after the slidding event of municipal solid wastes in 2005. It is necessary to reuse the TPA in the future through rehabilitation and revitalitation.The study is important due to the detail engineering design (DED) of new TPA which is still in an on going process, whereas need some consideration from technical and non-technical aspects. The result of geological survey showed that there is no signifi cant changes in geological condition, whether the changes were found in groundwater and surface water quality, before and after the slidding event. At the other side, the result of existing solid waste material showed that a high heavy metals content was found in the bulk material. It isalso found that the quality of degraded material yet is closed to compost, with a C/N ratio between 12,04 to 15,74. This compost-soil is recommended for daily cover soil at the TPA. So, before operating a new TPA, landfi ll mining must be done as initial activity.To reduce or minimize environmental impact the new TPA has to apply sanitary landfi ll method.Key words : biogeophysical, post slidding , Leuwigajah dumping area